A Ni-BiVO4 / g-C3N4 gas sensing material and preparation method thereof

The synthesis of Ni-BiVO4/g-C3N4 gas sensing material by one-step hydrothermal method solves the problems of low sensitivity and poor selectivity in detecting triethylamine, achieving high sensitivity and excellent selectivity, and has significant advantages in the detection of triethylamine.

CN115078462BActive Publication Date: 2025-03-18CHONGQING TECH & BUSINESS UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210755073.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-30
Publication Date
2025-03-18
Estimated Expiration
2042-06-30

AI Technical Summary

Technical Problem

The existing BiVO4 gas sensing materials have low sensitivity, poor selectivity and high operating temperature when detecting triethylamine, which limits their application.

Method used

The Ni-BiVO4/g-C3N4 gas sensing material was synthesized by a one-step hydrothermal method. By adding Ni2+ and g-C3N4, a polyhedral structure was formed to improve the structural stability and specific surface area of ​​the material.

Benefits of technology

Excellent selectivity and high sensitivity to triethylamine are achieved, with a sensitivity of 25.2, a minimum detection limit of 55.7 ppb, a fast response/recovery time, and good repeatability and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115078462B_ABST
    Figure CN115078462B_ABST
Patent Text Reader

Abstract

A Ni-BiVO4 / g-C3N4 gas sensing material, wherein the Ni-BiVO4 / g-C3N4 gas sensing material is a polyhedral structure, the particle size is about 100-300nm, and g-C3N4 is attached to the surface of the polyhedral structure, and the surface is rough. The Ni-BiVO4 / g-C3N4 gas sensing material in the present invention has a narrow bandgap width, a large specific surface area of ​​17.64cm2 / g, excellent selectivity for triethylamine, a sensitivity of 25.2 at a triethylamine concentration of 30ppm, a minimum detection limit of 55.7ppb, a fast response / recovery time, a response / recovery of 39s / 32s at a triethylamine concentration of 30ppm, and good repeatability and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas detection, and in particular to a Ni-BiVO4 / g-C3N4 gas sensing material and a preparation method thereof. Background Art

[0002] Triethylamine is a colorless, transparent liquid that emits a slight smoke in the air and has a strong ammonia smell. It is toxic and highly irritating. It is mainly used as a solvent, catalyst, biopharmaceutical, and synthetic dye in industry. Triethylamine can cause severe irritation to the respiratory tract and can even cause pulmonary edema or even death after inhalation. In addition, TEA can also be produced from the process of microbial degradation of dead fish and seafood. According to the regulations of the Occupational Safety and Health Administration (OSHA), the maximum allowable concentration of triethylamine in the air is 10 ppm. Therefore, the development of new sensors with fast response and good selectivity to TEA is crucial for biomedicine, food industry, and our daily life.

[0003] Bismuth vanadate (BiVO4) is an n-type ternary metal oxide semiconductor material with the characteristics of narrow bandgap, fast electron transfer and excellent optical properties. It is widely used in photocatalysts, lithium-ion batteries, gas sensors, photoelectrochemical devices, electronic devices and microwave absorbers. However, in the field of gas sensing, BiVO4 has high operating temperature (>300℃), low sensitivity and poor selectivity, which limits the application of BiVO4 in the sensor field.

[0004] According to the document “Morphology-Controlled Synthesis of BiVO4 Materials and Their Ethanol Gas Sensing Properties [J]”, DP Wang, CG Song. IEEE Acess. 8(2020) 24941-24947. (“Synthesis of BiVO4 Materials under Morphology Control and Their Ethanol Gas Sensing Properties”, DP Wang, CG Song, “IEEE Acess”, Issue 8, Pages 24941-24947, 2020), BiVO4 was synthesized by a one-step hydrothermal method with the addition of polyethylene glycol (PEG). The BiVO4 prepared with the addition of PEG1000 has the best selectivity for ethanol, with a response value of 4.23 to 200 ppm of ethanol, and the optimal operating temperature is 340 ℃.

[0005] According to the literature “Oxygen-Defective Ultrathin BiVO4 Nanosheets for Enhanced Gas Sensing[J]”, D. Yao, CW Dong, QM Bing, Y. Liu, FD Qu, et al. ACSAppl. Mater. Interfaces. 11(2019) 23495−23502. (“Oxygen-Defective Ultrathin BiVO4 Nanosheets for Enhanced Gas Sensing”, D. Yao, CW Dong, QM Bing, Y. Liu, FD Qu, et al., Materials Application Interfaces, Issue 11, Pages 23495−23502, 2019), two-dimensional BiVO4 nanosheets containing oxygen vacancies were prepared by a colloidal method. At 300 °C, the response value to 100 ppm acetone gas was about 7.1, and the minimum detection limit was 0.39 ppm. The literature ("Synthesis of bismuth vanadate nanocomposites and their research on triethylamine gas-sensitive myocardial infarction and matrix", Yang Xiaojun, Beijing University of Chemical Technology) prepared 6W-BiVO4 / rG05 composite materials by metal decomposition and hydrothermal synthesis, and the response value to TEA was 12.8, which is 5.12 times that of BiVO4. Based on this, it is necessary to seek sensor composite materials with higher sensitivity to triethylamine. Summary of the invention

[0006] The present invention aims to provide a Ni-BiVO4 / g-C3N4 gas sensing material, which has excellent sensitivity and selectivity for detecting triethylamine.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned Ni-BiVO4 / g-C3N4 gas sensing material.

[0008] The purpose of the present invention is achieved through the following technical solutions:

[0009] A Ni-BiVO4 / g-C3N4 gas sensing material, characterized in that: the Ni-BiVO4 / g-C3N4 gas sensing material is a polyhedral structure with a particle size of about 100-300nm, and g-C3N4 is attached to the surface of the polyhedral structure, and the surface is rough.

[0010] Furthermore, the above-mentioned Ni-BiVO4 / g-C3N4 gas sensing material is synthesized by a one-step hydrothermal method using ammonium metavanadate, bismuth nitrate, g-C3N4 and nickel nitrate as raw materials, wherein the molar ratio of nickel nitrate, ammonium metavanadate, bismuth nitrate and g-C3N4 is 0.04~0.2mmol:4mmol:4mmol:0.01g.

[0011] Preferably, the nickel nitrate, ammonium metavanadate, bismuth nitrate and g-C3N4 are in a molar ratio of 0.12mmol:4mmol:4mmol:0.01g

[0012] Furthermore, the preparation method of the above-mentioned Ni-BiVO4 / g-C3N4 gas sensing material is characterized in that: ammonium metavanadate and bismuth nitrate are added to deionized water, and after stirring and dissolving, ammonium dodecyl sulfate (SDS) is added, and after stirring, g-C3N4 is added, and after ultrasound, nickel nitrate is added, and then a one-step hydrothermal reaction is carried out.

[0013] When considering reducing energy consumption during the preparation process, we chose to use a one-step hydrothermal method to prepare the composite material. However, during the preparation process, we found that during the hydrothermal process, the generation of BiVO4 and the attachment of g-C3N4 were carried out simultaneously, which would result in the g-C3N4 being encapsulated into its structure during the BiVO4 forming process, resulting in less g-C3N4 attached to the surface and uneven morphology of BiVO4. In addition, g-C3N4 is prone to agglomeration at high temperatures and has poor dispersion.

[0014] In the present invention, Ni is added 2+ Replaced some Bi 3+ In addition to forming more oxygen vacancies, Ni-OV bonds are also formed in the system, which improves the structural stability of the composite material while shrinking the volume of the BiVO4 structure and inhibiting the entry of g-C3N4 into the crystal structure during the hydrothermal process, thereby ensuring that g-C3N4 almost exists on the surface of the structure; in addition, the anionic surfactant increases the charge density on the surface of the generated BiVO4. With the addition of nickel nitrate, the negative charge of the g-C3N4 surface is changed, and the surface repulsion of the same charge layer resists the intermolecular force, thereby improving the adhesion and dispersibility of g-C3N4 on the BiVO4 surface, thereby obtaining a larger specific surface area and more reactive sites.

[0015] Furthermore, the molar ratio of nickel nitrate, ammonium metavanadate, bismuth nitrate and g-C3N4 is 0.04~0.2mmol:4mmol:4mmol:0.01g. Preferably, the molar ratio of nickel nitrate, ammonium metavanadate, bismuth nitrate and g-C3N4 is 0.12mmol:4mmol:4mmol:0.01g.

[0016] Furthermore, the one-step hydrothermal reaction is to place the mixed solution at 180-200° C., keep the temperature for 8-10 hours, and naturally cool to room temperature after the reaction is completed.

[0017] Preferably, the one-step hydrothermal reaction is carried out at a temperature of 180° C. and kept warm for 9 hours.

[0018] Furthermore, the above g-C3N4 is obtained by calcining urea at 500°C for 2h and then grinding.

[0019] The most specific method is a method for preparing a Ni-BiVO4 / g-C3N4 gas sensing material, characterized by the following steps:

[0020] (1) Add ammonium metavanadate and bismuth nitrate to deionized water, stir magnetically for 30-40 minutes, add sodium dodecyl sulfate (SDS), stir and dissolve, add g-C3N4, ultrasonically treat for 30-50 minutes, then add nickel nitrate, stir magnetically until completely dissolved to form a mixed solution, wherein the molar volume ratio of ammonium metavanadate, bismuth nitrate and deionized water is 1mmol:1mmol:15mL, and the molar mass ratio of nickel nitrate, bismuth nitrate, SDS and g-C3N4 is 0.04~0.2mmol:4mmol:0.1g:0.01g;

[0021] (2) The mixed solution is transferred into a reactor and subjected to hydrothermal reaction at 180-200°C for 8-10 hours, then naturally cooled to room temperature, and after solid-liquid separation, dried and ground to obtain Ni-BiVO4 / g-C3N4.

[0022] Furthermore, the application of the above-mentioned Ni-BiVO4 / g-C3N4 gas sensing material is characterized in that it is used to detect triethylamine gas.

[0023] Furthermore, the optimal operating temperature of the above-mentioned Ni-BiVO4 / g-C3N4 gas sensing material is 230°C.

[0024] The present invention has the following technical effects:

[0025] The present invention adopts a one-step hydrothermal method to prepare the Ni-BiVO4 / g-C3N4 gas sensing material, which overcomes the technical problem that g-C3N4 agglomerates and is difficult to be evenly dispersed and attached to the surface of the material, so that the prepared Ni-BiVO4 / g-C3N4 gas sensing material has good size and structural uniformity, and g-C3N4 is evenly distributed on the surface of the material without agglomeration;

[0026] The Ni-BiVO4 / g-C3N4 gas sensing material of the present invention has a narrow bandgap and a large specific surface area of ​​17.64 cm2 / g, has excellent selectivity for triethylamine, has a sensitivity of 25.2 at a triethylamine concentration of 30 ppm, has a minimum detection limit of 55.7 ppb, has a fast response / recovery time of 39 s / 32 s at a triethylamine concentration of 30 ppm, and has good repeatability and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1: XRD patterns of BiVO4, BiVO4 / g-C3N4, 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4 and 5% Ni-BiVO4 / g-C3N4 samples.

[0028] Figure 2 : XPS full spectrum, Bi 4f spectrum, V 2p spectrum, Ni 2p spectrum and C 1s spectrum of 3% Ni-BiVO4 / g-C3N4.

[0029] Figure 3 : SEM image of 3% Ni-BiVO4 / g-C3N4.

[0030] Figure 4 : N2 adsorption-desorption isotherms of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 samples.

[0031] Figure 5 : Sensitivity of BiVO4, BiVO4 / g-C3N4, 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4 and 5% Ni-BiVO4 / g-C3N4 based gas sensors to 30 ppm triethylamine at different operating temperatures (130 ℃~330 ℃).

[0032] Figure 6 : Sensitivities of BiVO4, BiVO4 / g-C3N4, 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4, and 5% Ni-BiVO4 / g-C3N4 based gas sensors to different target gases at 30 ppm at their respective optimal temperatures.

[0033] Figure 7 : Dynamic response recovery curves of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 gas sensors to 1~30 ppm triethylamine gas at their respective optimal temperatures;

[0034] Figure 8 : Linear fitting of the gas responses of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 gas sensors to 1-9 ppm triethylamine.

[0035] Fig. 9 : Response recovery curves of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 gas sensors to 30 ppm triethylamine gas at 230 ℃.

[0036] Fig.10 : Five-cycle response-recovery curves of 3% Ni-BiVO4 / g-C3N4 gas sensor to 30 ppm triethylamine at 230 ℃.

[0037] Fig.11 : XPS O 1s spectrum of 3% Ni-BiVO4 / g-C3N4 sample.

[0038] Fig.12 : UV-visible absorption spectra of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 samples. DETAILED DESCRIPTION

[0039] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0040] Example 1

[0041] A method for preparing a Ni-BiVO4 / g-C3N4 gas sensing material is carried out according to the following steps:

[0042] (1) Add 4 mmol of ammonium metavanadate and 4 mol of bismuth nitrate to 60 mL of deionized water, stir magnetically for 30 min, add 0.1 g of sodium dodecyl sulfate (SDS), stir to dissolve, add 0.01 g of g-C3N4, ultrasonically treat for 30 min, then add 0.12 mmol of nickel nitrate, stir magnetically until completely dissolved to form a mixed solution;

[0043] (2) The mixed solution was transferred into a reactor and subjected to hydrothermal reaction at 180°C for 9 h, then naturally cooled to room temperature, and after solid-liquid separation, dried and ground, a Ni-BiVO4 / g-C3N4 composite material was obtained, which was recorded as 3% Ni-BiVO4 / g-C3N4.

[0044] The other conditions remained unchanged, but the amount of nickel nitrate added was changed to 0.04 mmol and 0.2 mmol respectively. The prepared Ni-BiVO4 / g-C3N4 composite materials were recorded as 1%Ni-BiVO4 / g-C3N4 and 5%Ni-BiVO4 / g-C3N4 respectively.

[0045] In order to verify the technical effect of the Ni-BiVO4 / g-C3N4 gas sensing material of the present invention, a method for preparing bismuth vanadate (BiVO4) and a method for preparing bismuth vanadate composite carbon trinitrogen tetrakis (BiVO4 / g-C3N4) are provided below to obtain bismuth vanadate and bismuth vanadate composite carbon trinitrogen tetrakis gas sensing materials for comparison.

[0046] Comparative Example 1

[0047] The preparation method of BiVO4 comprises the following steps:

[0048] 4 mmol of ammonium metavanadate and 4 mmol of bismuth nitrate were added to 60 ml of deionized water, and then sodium dodecyl sulfate (SDS) was added. The mixture was stirred magnetically for 30 minutes and then transferred into a reactor. The mixture was heated to 180 °C and kept warm for 9 hours. The mixture was cooled to room temperature, and bismuth vanadate (BiVO4) powder was obtained by solid-liquid separation, drying and grinding.

[0049] Comparative Example 2

[0050] 4 mmol ammonium metavanadate and 4 mmol bismuth nitrate were added to 60 ml deionized water, sodium dodecyl sulfate (SDS) was added, stirred evenly, and then 0.01 g g-C3N4 was added, ultrasonicated for 30 minutes, transferred to a reactor, heated to 180°C, kept warm for 9 hours, cooled to room temperature, and subjected to solid-liquid separation, drying, and grinding to obtain a BiVO4 / g-C3N4 composite material. In the prepared BiVO4 / g-C3N4, since the attachment of g-C3N4 and the formation of the BiVO4 structure are carried out simultaneously, part of the g-C3N4 is coated inside by BiVO4, which affects the structural uniformity of BiVO4, and the amount of g-C3N4 attached to its surface is reduced, so that its detection performance is not ideal.

[0051] The performance of BiVO4 and BiVO4 / g-C3N4 prepared in Comparative Examples 1 and 2 was compared with that of 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4 and 5% Ni-BiVO4 / g-C3N4 prepared in Example 1.

[0052] The crystal phase, morphology, specific surface area and chemical composition of the samples were characterized by X-ray diffraction (XRD, Max-1200, Japan), scanning electron microscopy (SEM, JEOL model JSM-6490), transmission electron microscopy (TEM, JEM-2010), N2 adsorption-desorption instrument (ASAP 2020, USA), UV (UV-2700) and X-ray photoelectron spectroscopy (XPS, Thermo ESCALAB 250, USA).

[0053] Figure 1 The XRD patterns of BiVO4, BiVO4 / g-C3N4, 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4 and 5% Ni-BiVO4 / g-C3N4 samples are shown below. Figure 1As shown in the figure, the main diffraction peaks of the XRD pattern at 2θ=18.92°, 30.60°, 30.62°, 34.60°, 35.28°, 39.98°, 42.52°, 46.06°, 46.84°, 50.30°, 53.36° and 58.54° correspond to BiVO4 (011), (−121), (040), (200), (002), (112), (051), (132), (042), (202), (161), (071) crystal planes (JCPDS No.14-0688), indicating that the BiVO4 nanomaterials were successfully synthesized; the peak of g-C3N4 appears at 2θ=27.06. Obviously, in the composite g-C3N4 sample, the diffraction peak corresponding to the (131) crystal plane increases in intensity, and there are no other impurity peaks, indicating that the BiVO4 / g-C3N4 nanomaterial is successfully composited. 2+ Less, and Ni 2+ The small radius results in unclear peak intensity, and no diffraction peak related to Ni appears in the Ni-BiVO4 / g-C3N4 sample.

[0054] XPS spectroscopy was used to characterize the elemental composition and the chemical valence states of each element in Ni-BiVO4 / g-C3N4. Figure 2 (a) is the full XPS spectrum of Ni-BiVO4 / g-C3N4, which clearly shows the presence of Bi, V, O, Ni, C and N elements in the prepared product; Figure 2 (b) XPS Bi 4f spectrum of 3% Ni-BiVO4 / g-C3N4. The two fitting peaks at 160.15 and 165.48 eV correspond to Bi 4f 7 / 2 and Bi 4f 5 / 2 , indicating that the Bi element in the sample is Bi 3+ Form exists; Figure 2 (c) XPS V 2p spectrum of 3% Ni-BiVO4 / g-C3N4. The two fitting peaks at 517.52 and 530.65 eV correspond to V 2p 3 / 2 and V2p 1 / 2 , indicating that the V element in the sample is V 5+ Form exists; Figure 2 (d) XPS N 1s spectrum of 3% Ni-BiVO4 / g-C3N4. The characteristic peaks at 398.83, 399.83 and 400.72 eV correspond to sp 2The hybridized aromatic N elements, the N elements bonded to C atoms in the form of N-(C)3, and the N elements in the NH structure, have an unclear N 1s peak in the full spectrum due to the small amount of g-C3N4 complexed. Figure 2 (e) XPS Ni 2p spectrum of 3% Ni-BiVO4 / g-C3N4. The two fitting peaks at 859.90 and 873.29 eV correspond to Ni 2p 3 / 2 and Ni 2p 1 / 2 , indicating that Ni element is Ni 2+ form of doping into the sample. Figure 2 (f) is the C 1s spectrum of 3% Ni-BiVO4 / g-C3N4 sample, sp 2 The binding energies of CC, CO and NC=N bonds are 282.18, 283.92 and 285.45 eV respectively. XPS results show that Ni-BiVO4 / g-C3N4 composites were successfully synthesized.

[0055] Figure 3 This is the SEM image of 3% Ni-BiVO4 / g-C3N4. Figure 3 (a) It can be seen that a large-scale, uniform-sized, and regularly structured 3% Ni-BiVO4 / g-C3N4 composite material was successfully synthesized; Figure 3 (b) 3% Ni-BiVO4 / g-C3N4 presents polyhedrons with a diameter of about 100-300 nm and a rough surface; Figure 3 (c) shows that the polyhedral 3%Ni-BiVO4 / g-C3N4 is assembled from many nanoparticles, among which g-C3N4 particles are uniformly attached to the surface.

[0056] Figure 4 The N2 adsorption-desorption isotherms of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 samples show that the specific surface areas of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 are 1.65 m 2 / g, 3.01 m 2 / g and 17.64 m 2 / g, the results show that the composite g-C3N4 can increase the specific surface area of ​​the material, and doping Ni 2+ The synergistic effect with g-C3N4 on the specific surface area is more obvious. Compared with BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 composites have larger specific surface areas, which can provide more gas molecule adsorption-desorption sites and diffusion paths, thereby enhancing the gas sensing performance of the sensor.

[0057] Figure 5 The sensitivity of BiVO4, BiVO4 / g-C3N4, 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4 and 5% Ni-BiVO4 / g-C3N4 based gas sensors to 30 ppm triethylamine at different operating temperatures (130 ℃ ~ 330 ℃). It can be seen that: Figure 5 The sensitivity of BiVO4, BiVO4 / g-C3N4 and Ni-BiVO4 / g-C3N4 increases first and then decreases, reaching the maximum response at 280 ℃, 230 ℃ and 230 ℃ respectively. The sensitivity (S) of BiVO4, BiVO4 / g-C3N4 and Ni-BiVO4 / g-C3N4 based gas sensors to 30 ppm triethylamine at the optimal temperature (T) are: BiVO4 (S=2.4, T=280 ℃), BiVO4 / g-C3N4 (S=8.5, T=230 ℃), 1% Ni-BiVO4 / g-C3N4 (S=16.3, 230 ℃), 3% Ni-BiVO4 / g-C3N4 (S=25.2, T=230 ℃), 5% Ni-BiVO4 / g-C3N4 (S=10.4, T=230 ℃). The results show that compounding a certain amount of g-C3N4 can reduce the working temperature of the material and improve the performance of triethylamine, and doping with appropriate Ni 2+ It can effectively improve the gas sensing performance of the sensor, but if Ni 2+ A large amount of doping will lead to a decrease in detection performance.

[0058] Figure 6 The sensitivity of BiVO4, BiVO4 / g-C3N4, 1% Ni-BiVO4 / g-C3N4, 3% Ni-BiVO4 / g-C3N4 and 5% Ni-BiVO4 / g-C3N4 based gas sensors to different target gases (benzene, acetone, formaldehyde, triethylamine, ethanol, toluene) at 30 ppm at their respective optimal operating temperatures is shown in Table 1. Compared with BiVO4 and BiVO4 / g-C3N4 based gas sensors, the 3% Ni-BiVO4 / g-C3N4 based gas sensor has the highest sensitivity to triethylamine gas (sensitivity is 25.2) among the Ni-BiVO4 / g-C3N4 based gas sensors, which is also much higher than its sensitivity to other gases, indicating that the 3% Ni-BiVO4 / g-C3N4 based gas sensor has good selectivity to triethylamine gas.

[0059] Figure 7The dynamic response recovery curves of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 based gas sensors to 1-30 ppm triethylamine gas at their respective optimal working temperatures are shown in Table 1. The sensitivities of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 based gas sensors are 1.4, 1.6, 2.9 (1 ppm), 1.5, 1.8, 4.4 (3 ppm), 1.7, 2.3, 6.5 (5 ppm), 1.8, 3.2, 8.8 (7 ppm), 1.9, 3.8, 11.1 (9 ppm), 2.0, 5.3, 16.1 (15 ppm), 2.4, 8.5, 25.2 (30 ppm). Based on the above results, the Ni-BiVO4 / g-C3N4-based gas sensor has significantly higher sensitivity to triethylamine gas than BiVO4 and BiVO4 / g-C3N4 at all triethylamine gas concentrations, among which the 3% Ni-BiVO4 / g-C3N4-based gas sensor has the most significant effect, indicating that the appropriate amount of Ni doped 2+ It can effectively improve the sensitivity of the material.

[0060] Figure 8 Figure 2 is the fitting curve of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 based gas sensors for 1-9 ppm triethylamine gas. As can be seen from the figure, the correlation coefficients (R 2 ) values ​​are all greater than 0.99, indicating that all sensors have good linear responses to triethylamine. According to the triple noise value, the lowest detection limits can be obtained: BiVO4 (0.5069 ppm), BiVO4 / g-C3N4 (0.1169 ppm), 3% Ni-BiVO4 / g-C3N4 (0.0557 ppm). It can be concluded that appropriate amounts of g-C3N4 and Ni doping can reduce the detection limit, and the minimum detection limit of 3% Ni-BiVO4 / g-C3N4-based gas sensor for triethylamine is 55.7 ppb, which has great advantages in detecting low concentrations of triethylamine.

[0061] Fig. 9 (a)-(c) are the response recovery curves of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 based gas sensors to 30 ppm triethylamine gas at their optimal working temperature. The response recovery times of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 to 30 ppm triethylamine are 72 s / 115 s, 62 s / 71 s and 39 s / 32 s, respectively, indicating that the composite g-C3N4 and doped Ni 2+The absorption of target gas by BiVO4 can be accelerated, thus shortening the response recovery time.

[0062] Fig.10 The 5-cycle response-recovery curve of 3% Ni-BiVO4 / g-C3N4 based gas sensor to 30 ppm triethylamine at its optimal operating temperature. The test method is: pass triethylamine gas 5 times and then replace air 5 times. It can be seen from the figure that after 5 consecutive gas-sensitive tests, the response recovery characteristics can be almost repeated, and the sensitivity remains stable, indicating that the 3% Ni-BiVO4 / g-C3N4 based gas sensor has good repeatability and stability.

[0063] Fig.11 The XPS O 1s spectrum of 3% Ni-BiVO4 / g-C3N4 shows three different types of oxygen (lattice oxygen, defect oxygen and chemically adsorbed oxygen) at 528.99, 530.76 and 533.09 eV respectively. Lattice oxygen is very stable and has no effect on gas sensing performance. Defective oxygen and chemically adsorbed oxygen are very active and will affect gas sensing performance. As can be seen from the figure, the total proportion of defective oxygen and chemically adsorbed oxygen in 3% Ni-BiVO4 / g-C3N4 is 67% respectively. The high proportion of defective oxygen and chemically adsorbed oxygen will enhance the surface activity of the sensing material, thereby enhancing the gas sensing performance of 3% Ni-BiVO4 / g-C3N4 material to triethylamine.

[0064] Fig.12 The UV-visible absorption spectra of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 samples are shown in Figure 2. The maximum absorption wavelengths of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 are 552.8 nm, 563.1 nm and 572.4 nm respectively, obtained by the intercept method. Compared with BiVO4, the absorption bands of BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 are red-shifted, and the absorption range moves to the visible light region with longer wavelengths. This indicates that the composite g-C3N4 and doped Ni 2+ It can improve the light absorption capacity of BiVO4 in the visible light region. According to the maximum absorption wavelength (intercept method), it can be estimated that the bandgap widths of BiVO4, BiVO4 / g-C3N4 and 3% Ni-BiVO4 / g-C3N4 are 2.24, 2.20 and 2.16 eV respectively. It can be seen that the specific method of compounding g-C3N4 and doping Ni 2+ The bandgap width of the material is reduced. As the bandgap width decreases, the energy required for electrons to transition to the conduction band decreases, thereby improving the gas sensing performance of the 3% Ni-BiVO4 / g-C3N4 composite material.

[0065] Example 2

[0066] A method for preparing a Ni-BiVO4 / g-C3N4 gas sensing material is carried out according to the following steps:

[0067] (1) Add ammonium metavanadate and bismuth nitrate to deionized water, stir magnetically for 40 min, add sodium dodecyl sulfate (SDS), stir and dissolve, add g-C3N4, ultrasonically treat for 50 min, then add nickel nitrate, stir magnetically until completely dissolved to form a mixed solution, wherein the molar volume ratio of ammonium metavanadate, bismuth nitrate and deionized water is 1 mmol: 1 mmol: 15 mL, and the molar mass ratio of nickel nitrate, bismuth nitrate, SDS and g-C3N4 is 0.08 mmol: 4 mmol: 0.1 g: 0.01 g;

[0068] (2) The mixed solution was transferred into a reactor and subjected to hydrothermal reaction at 200°C for 8 h, then naturally cooled to room temperature, and after solid-liquid separation, dried and ground to obtain 2% Ni-BiVO4 / g-C3N4.

[0069] Example 3

[0070] A method for preparing a Ni-BiVO4 / g-C3N4 gas sensing material is carried out according to the following steps:

[0071] (1) Add ammonium metavanadate and bismuth nitrate to deionized water, stir magnetically for 35 min, add sodium dodecyl sulfate (SDS), stir and dissolve, add g-C3N4, ultrasonically treat for 40 min, then add nickel nitrate, stir magnetically until completely dissolved to form a mixed solution, wherein the molar volume ratio of ammonium metavanadate, bismuth nitrate and deionized water is 1 mmol: 1 mmol: 15 mL, and the molar mass ratio of nickel nitrate, bismuth nitrate, SDS and g-C3N4 is 0.16 mmol: 4 mmol: 0.1 g: 0.01 g;

[0072] (2) The mixed solution was transferred into a reactor and subjected to hydrothermal reaction at 190°C for 10 h, then naturally cooled to room temperature, and after solid-liquid separation, dried and ground, 4% Ni-BiVO4 / g-C3N4 was obtained.

Claims

1. A method for preparing a Ni-BiVO4 / g-C3N4 gas sensing material, characterized in that: Proceed as follows: (1) adding ammonium metavanadate and bismuth nitrate to deionized water, stirring magnetically for 30-40 minutes, adding sodium dodecyl sulfate (SDS), stirring and dissolving, adding g-C3N4, ultrasonically treating for 30-50 minutes, and then adding nickel nitrate, stirring magnetically until completely dissolved to form a mixed solution, wherein the molar volume ratio of ammonium metavanadate, bismuth nitrate and deionized water is 1mmol:1mmol:15mL, and the molar mass ratio of nickel nitrate, bismuth nitrate, SDS and g-C3N4 is 0.04-0.2mmol:4mmol:0.1g:0.01g, and the g-C3N4 is obtained by grinding after calcining urea at 500°C for 2h; (2) The mixed solution is transferred into a reactor and subjected to a hydrothermal reaction at 180-200°C for 8-10 hours, and then naturally cooled to room temperature. After solid-liquid separation, the mixture is dried and ground to obtain Ni-BiVO4 / g-C3N4; The prepared Ni-BiVO4 / g-C3N4 material has a polyhedral structure and a particle size of 100-300nm. The g-C3N4 is attached to the surface of the polyhedral structure and has a rough surface, and is used for detecting triethylamine gas.

2. Application of the Ni-BiVO4 / g-C3N4 gas sensing material prepared by the method according to claim 1 in detecting triethylamine gas.

3. An application of the Ni-BiVO4 / g-C3N4 gas sensing material as claimed in claim 2 in detecting triethylamine gas, characterized in that: The operating temperature of the Ni-BiVO4 / g-C3N4 gas sensing material is 230°C.

Citation Information

Patent Citations

  • Preparation of device based on g-C3N4 / Mo: BiVO4 and CuS

    CN113176314A